Examination of the Relationship between Childhood Trauma and Psychological Resilience in Preschool Teachers - Hatice Ozaslan, Rabia Seyma Gun, Gulumser Gultekin Akduman (Educational Process: International Journal)
Background/purpose – This paper investigated the relationship between childhood trauma and psychological resilience in preschool teachers. The study also determined whether psychological resilience depended on age.